Effects of Miniaturization of the Summer Phytoplankton Community on the Marine Ecosystem in the Northern East China Sea - Kyung-Woo Park; Hyun-Ju Oh; Su-Yeon Moon; Man-Ho Yoo; Seok-Hyun Youn (Journal of Marine Science and Engineering, 2022)
After the construction of the Three Gorges Dam (Changjiang River), the northern East China Sea has been exposed to major environmental changes in the summer due to climate change and freshwater control. However, little is known regarding phytoplankton in this area. Here, we investigated differences in the summer phytoplankton-community structure as a consequence of marine-environment changes from 2016 to 2020. In the 2000s, the key dominant species in the summer phytoplankton community in the northern East China Sea were diatoms and dinoflagellates. In this study, however, nanoflagellates of ≤20 µm were identified as the dominant species throughout the survey period, with abundances ranging from 43.1 to 69.7%. This change in the phytoplankton-community structure may be ascribed to low nutrient concentrations in the area, especially phosphate, which was below the detection limit, seriously hampering phytoplankton growth. The relative contribution of picophytoplankton to the total chlorophyll a biomass was highest in the surface mixed layer with low nutrient concentrations. Spatially, higher percentages were observed along the east-side stations than the west-side stations, where nutrient concentrations were relatively high. Conclusively, decreased nutrients led to phytoplankton miniaturization. Accordingly, as the dominance of picophytoplankton increases, energy transfer is expected to decrease at the upper trophic level.